Life Features of Uzbek Folk Pedagogy - Bozorova Muslima Kadyrovna (Researchparks Publishing, 2021)
The article describes the features of Uzbek folk pedagogy, the theoretical foundations of the gradual formation of social skills among young people, the issues of antiquity, periodicity, modernity, rationality, nationality, culture, religion, worldview, harmony, solidarity in the reforms of the existing education system of the Republic of Uzbekistan.